Factors Affecting on the Restructuring of Vietnamese Textile and Garment Enterprises - Long, Pham Dinh; Cuong, Pham Dinh (International Journal of Economics and Financial Issues, 2017)
The challenges and difficulties which the Vietnamese textile and garment enterprises have been facing recently result not only from objective external environment such as the requirement to expand the market, international economic integration and the sustainable development trend but also from the internal environment of enterprises such as the inadequacies and weaknesses of the process of production and business activities, the organizational structure, capital structure in terms of global value added chain, technological level, labor productivity, especially the requirement of innovation in approaches to management. Consequently, restructuring has been addressed by many researchers and the Vietnamese textile and garment enterprises. In fact, restructuring is always affected by many factors. However, identifying such factors is unclear and unspecific. The extent of their influences has not been clarified and tested. If the Vietnamese textile and garment enterprises want to conduct the restructuring successfully, it is necessary to do research into the extent that factors affecting their restructuring. Keywords: Restructuring, Vietnamese textile and garment enterprises. JEL Classifications: M10, M21